2020
DOI: 10.24018/ejbio.2020.1.5.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extended Transit and Temperature Variations on EID50 Values of Thermostable NDVI-2 Vaccines

Abstract: Temperature alterations due to poor cold keeping condition have consistently posed a challenge to vaccines dose EID50 titre value. The sensitivity of Newcastle disease vaccine to temperature variations due to poor cold storage condition in rural settings, led to the development of the NDVI-2 thermostable vaccine, which is known to exhibit a thermostability of 3 hours at 56 °C. In this study, three Newcastle disease vaccines (NDVI-2) with EID50 titre per dose values of log10 EID50 7.7, 7.6 and 6.75 respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…The re-validated vaccine final EID 50 titre per dose values were well within the acceptable EID 50 potency titre value for NDVI-2 ( 1), incooperated into these NDVI-2 vaccines batches while being compounded as observed in this study, were able to carter for the vaccine EID 50 titre loss observed (Table 2). Our finding and that of [10], is a further confirmation of the robustness, and integrity NDVI-2 vaccine, produced by the National Veterinary Research Institute Vom, Nigeria. It is thus suggested that for all vaccines, be it thermolabile or thermostable, that extra EID 50 value of about 1 to 2 EID 50 logarithm values be in-cooperated to carter for possible EID 50 titre loss that might occur due to poor cold vaccine storage conditions, especially in regions of the world with limited, or poor electricity supply.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The re-validated vaccine final EID 50 titre per dose values were well within the acceptable EID 50 potency titre value for NDVI-2 ( 1), incooperated into these NDVI-2 vaccines batches while being compounded as observed in this study, were able to carter for the vaccine EID 50 titre loss observed (Table 2). Our finding and that of [10], is a further confirmation of the robustness, and integrity NDVI-2 vaccine, produced by the National Veterinary Research Institute Vom, Nigeria. It is thus suggested that for all vaccines, be it thermolabile or thermostable, that extra EID 50 value of about 1 to 2 EID 50 logarithm values be in-cooperated to carter for possible EID 50 titre loss that might occur due to poor cold vaccine storage conditions, especially in regions of the world with limited, or poor electricity supply.…”
Section: Discussionsupporting
confidence: 83%
“…The use of the NDVI-2 thermostable vaccine under poor cold storage conditions does not entail or encourage complete or absolute negligence of standard vaccine cold storage condition; despite the NDVI-2 vaccine thermostable nature. This is also in agreement with the findings of [10] where it was reported that the thermostable nature of the NDVI-2 vaccine does not exempt it from EID 50 titre value drop. It is therefore important to note that a thermostable vaccine must be handled with same care accorded to other thermo-sensitive biological products; thus, thermostable vaccine such as NDVI-2 cannot be expose to sunlight and frequent alterations in temperature and still be expected to remain potent [1].…”
Section: Determination Of Eid 50 Valuessupporting
confidence: 93%
See 2 more Smart Citations